1999
DOI: 10.1089/104454999315178
|View full text |Cite
|
Sign up to set email alerts
|

A His2AvDGFP Fusion Gene Complements a Lethal His2AvD Mutant Allele and Provides an in Vivo Marker for Drosophila Chromosome Behavior

Abstract: We have generated Drosophila melanogaster lines carrying a modified genomic fragment which encodes the D. melanogaster variant H2A.F/Z class histone, His2AvD, fused to the green fluorescent protein (GFP) of the jellyfish Aequorea victoria. We show here that the fusion protein consists of functional GFP and functional histone His2AvD. The His2AvD portion of the fusion gene was shown to be functional by rescue of His2AvD mutant lethality. Fluorescence of the fusion protein in vivo was observed in embryonic cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(171 citation statements)
references
References 20 publications
2
169
0
Order By: Relevance
“…To examine more directly how the absence of CENP-meta affects chromosome movement, chromosomes in CENP-meta deficient embryos were marked by introducing a stably inherited histone-2A-variant-GFP (Clarkson and Saint 1999). Real-time images of these embryos (videos available at http://www.jcb.org/cgi/content/full/150/1/1/DC1) revealed that congression of the fluorescently marked chromosomes appears to proceed relatively normally in cmet lx1 mutant embryos, but the chromosomes do not stably persist at the metaphase plate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine more directly how the absence of CENP-meta affects chromosome movement, chromosomes in CENP-meta deficient embryos were marked by introducing a stably inherited histone-2A-variant-GFP (Clarkson and Saint 1999). Real-time images of these embryos (videos available at http://www.jcb.org/cgi/content/full/150/1/1/DC1) revealed that congression of the fluorescently marked chromosomes appears to proceed relatively normally in cmet lx1 mutant embryos, but the chromosomes do not stably persist at the metaphase plate.…”
Section: Resultsmentioning
confidence: 99%
“…Germ-line clones were induced using FRT-ovoD1 and hsFLPase following Chou and Perrimon 1996. Clones containing chromosomes illuminated by histone-2A-var-GFP (a kind gift of Rob Saint, University of Adelaide; Clarkson and Saint 1999) were generated using FRT-cmet/SM1;hisvar-GFP/TM6B and hsFLPase/Y, FRT-ovoD1/CyO. Real-time movies were made using manually dechorionated embryos in heptane glue (Santamaria, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…The GAL4-e33c upstream activating sequence (UAS)-gfp strain was generated by crossing flies carrying the GAL4-e33c enhancer trap (27) to flies carrying the gfp transgene under control of the UAS (GAL4 response element), thus achieving constitutive GFP expression in hemolymph and lymph glands hemocytes. For in vivo transfers, we used two GFP-expressing lines: His::GFP [ubiquitous expression of a fusion protein between histone His2AvD and GFP (28)] and Tum-l; His::GFP (generated by standard crossing). Stocks were fed standard cornmeal, molasses, yeast, and agar medium and were maintained at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the dynamics of Nup107 during mitosis, we first followed by time-lapse scanning confocal microscopy (TLSCM) the last three syncytial mitotic cycles (cycles 10 -13) of early Drosophila embryos expressing mRFP-Nup107 together with the GFP-tagged histone H2A variant His2AvD (Clarkson and Saint, 1999). Representative panels from one cleavage cycle (cycle 12) are shown in Figure 2A (Supplemental Movie 1).…”
Section: Dynamics Of Drosophila Nup107 An Essential Nuclear Pore Promentioning
confidence: 99%